From assessment to policy analysis: A case study. Diagnosis of the vocational and technical education and training sub-system in Cariwak - Atchoarena, David (International Institute for Educational Planning, 1994)
This case study was developed as the basis for review and discussion of the methodology used for diagnosis in the area of technical and vocational education and training (TVET)
Keywords: Educational policies